Analytical Model to Measure the Effectiveness of Epoxy Adhesive in Cold Concrete Joints Through Compression Tests on Cylindrical Specimens - Campos Velarde, Lucía Margarita (2024)
Cold joints represent concrete flaws resulting from different pouring times needed to complete a structural unit. The current investigation focuses on examining the reduction in compressive strength of concrete with cold joints at different pouring intervals through the development of an analytical model that describes the effectiveness of the use of two adhesion bridges to bond the new concrete to old concrete. To obtain the necessary data, compressive strength experimentation of concrete specimens with cold joints is carried out. The samples were manufactured under on-site conditions to ensure that the results presented faithfully reflect reality in construction projects in Lima, Peru. Furthermore, ANSYS is used to model the samples, which facilitates a more detailed analysis of their strength, and allows obtaining the friction coefficient of the interface zone as a function of the applied load. Processing the results revealed a compression strength decrease of up to 30%, regardless of whether specimens had cold joints treated with epoxy or not. As a result, the use of epoxy adhesive may be dispensable, especially if the pouring of the old concrete occurs within the first two days.